Spontaneous hypoglycemia: a review - Shefin, Sultana Marufa; Qureshi, Nazmul Kabir; Mir, Ahmed Salam; Amin, Ahasnul Haq; Ahmed, Tareen; Afsana, Faria; Alam, Md Shah; Akter, Farhana; Emran, Md Shah; Hossain, Tanjina; Khan, Md Shahjamal; Mustari, Marufa; et al. (IMC Journal of Medical Science, 2019)
Spontaneous hypoglycemia is an important entity that may affect multiple organs. The differential diagnosis is broad in individuals with hypoglycemia in the absence of diabetes mellitus. Multiple etiologies may be present concurrently. Drugs, critical illnesses, hormone deficiencies, and non-islet cell tumors should be considered in those who are ill or taking medications. In apparently healthy individuals, endogenous hyperinsulinism due to insulinoma, functional β-cell disorders, or insulin autoimmune conditions are possible, as are accidental, surreptitious or factitious causes of hypoglycemia. Investigations should be guided by clinical scenario. Irrespective of the exact cause of the spontaneous hypoglycemia, treatment consists of correcting the glycemic state and preventing recurrence by alleviating underlying pathology. This review discusses the causes, diagnosis and management of spontaneous hypoglycemia. IMC J Med Sci 2019; 13(1): 001